IMPROVING PERSONAL BRANDING CAPACITY ON INSTAGRAM SOCIAL MEDIA FOR STUDENTS OF SMAN 1 SUMEDANG - Tresnawati, Yanti Susila; Iqbal, Mochamad (LPM Universitas Pasundan, 2023)
Personal branding can be built and needs to be owned even when still in school, The uniqueness of students lies in their ability to explore various things with a high spirit of exploration. This is reflected in their high involvement in Instagram social media, and can be utilized through increasing personal branding capacity. Students of SMA Negeri 1 Sumedang have the potential to develop, but are still faced with problems: 1. Need knowledge about personal branding on Instagram social media, 2. Do not understand the application of strategies for building personal branding on Instagram social media, 3. Need to be given a tutorial to start personal branding and become a wise social media user. The solutions determined are as follows: 1) Increased knowledge about personal branding on Instagram social media. 2) Increased ability to apply strategies for building personal branding on Instagram social media. 3) Improvement to start personal branding and become a wise social media user. The approach methods used include; Training, Technical Guidance. The results of the activity show, Increasing knowledge about personal branding on Instagram social media, increasing capacity in implementing strategies to build personal branding on Instagram social media, and increasing capacity to become wise social media users from SMA Negeri 1 Sumedang Students.